Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 97891 by pranesh last updated on 10/Jun/20

Commented by mr W last updated on 10/Jun/20

y=e^x −1

y=ex1

Commented by bemath last updated on 10/Jun/20

λ^2 −1=0  λ = ± 1  y_h  = Ae^x  + Be^(−x)   particular y_p  = ax+b  y′ = a , y′′ = 0  0−(ax+b) = 1 ⇔ { ((a = 0)),((b=−1)) :}  y_c  = Ae^x  + Be^(−x) −1  x = 0 , y = 0  ⇔ 0 = A+B−1 , A+B = 1  y_c  = Ae^x + (1−A)e^(−x) −1

λ21=0λ=±1yh=Aex+Bexparticularyp=ax+by=a,y=00(ax+b)=1{a=0b=1yc=Aex+Bex1x=0,y=00=A+B1,A+B=1yc=Aex+(1A)ex1

Commented by mr W last updated on 10/Jun/20

A must be equal to 1, otherweise  lim_(x→−∞) y=0+(1−A)∞−1=∞≠a

Amustbeequalto1,otherweiselimxy=0+(1A)1=a

Commented by bemath last updated on 10/Jun/20

how to get A = 1?

howtogetA=1?

Commented by mr W last updated on 10/Jun/20

such that lim_(x→−∞)  y ↛ ∞, the term  e^(−x)  must vanish, therefore 1−A=0.

suchthatlimxy,thetermexmustvanish,therefore1A=0.

Commented by bemath last updated on 10/Jun/20

oo yes sir. thank you

ooyessir.thankyou

Terms of Service

Privacy Policy

Contact: info@tinkutara.com